Peran Museum Bank Indonesia sebagai Sarana Wisata Edukasi Sejarah - Meisya Rakhma Aqiila; Musa Pelu (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2026)
. This study analyzes the role of the Bank Indonesia Museum (MuBI) in Jakarta as a historical educational tourism facility. Using a qualitative approach with a case study method, data were collected through observation, interviews, and documentation. The findings show that MuBI serves as an effective historical learning space through three main aspects. First, its numismatic and non-numismatic collections contain historical value and are closely related to everyday life. Second, information is presented with the support of interactive technologies, including touchscreen displays, sound domes, magic books, interactive floors and screens, and immersive spaces, making the learning process more engaging and contextual. Third, MuBI offers public programs based on edutainment, combining education and entertainment. Visitor perceptions indicate that the museum provides an attractive learning experience through its collections, spatial arrangement, and technology. However, some visitors still find the central banking material difficult to understand, while visit motivations are often recreational and influenced by visual appeal. Overall, MuBI has effectively integrated preservation, education, and recreation, although material simplification and communication strategies still need improvement.